Promotion Mix Strategy to Increase Inpatient Visits at F.L. Tobing General Hospital, Sibolga in 2025 - Ade Afifah Aliyah; Rahmad Gurusinga; Sri Melda Bangun; Rahmadani Sitepu; Raisha Octavariny (JURNAL KESMAS DAN GIZI (JKG), 2026)
The implementation of hospital promotion strategies through public relations and brand management at F.L. Tobing General Hospital, Sibolga, is influenced by various inhibiting and supporting factors. The main inhibiting factors include limited marketing budgets, a lack of competent human resources in public relations and brand management, suboptimal use of digital media, intense competition from more aggressive private hospitals, and weak promotional effectiveness evaluation mechanisms. Meanwhile, supporting factors include F.L. Tobing General Hospital's status as a government referral hospital, support from local government policies, opportunities for collaboration with various institutions, and increasing management awareness of the importance of promotion and strengthening brand image to increase hospital competitiveness. This study used a descriptive qualitative approach with triangulation of data sources within the F.L. Tobing General Hospital's work area, involving one key informant and 11 triangulation informants, and data collection techniques through observation, interviews, and documentation. The results showed that the advertising strategy was still dominated by internal media such as banners, posters, and brochures. Inpatient sales promotion is conducted through non-tariff promotions due to regulations, including simplified BPJS and insurance administration, service package information, and supporting facilities. Personal selling through empathetic interactions with healthcare workers, oriented toward patient-centered care, is the most influential strategy in building trust and inpatient care decisions. Direct digital marketing through WhatsApp and a reservation system supports rapid information access and increases patient satisfaction and loyalty. Public relations strategies play a crucial role in building image, encouraging positive word of mouth, and increasing inpatient visits. Continuous improvement of interpersonal communication skills, optimization of digital media, and contextual health education for patients' families are recommended.